Chloroplast ATP Synthase Modulation of the Thylakoid Proton Motive Force: Implications for Photosystem I and Photosystem II Photoprotection - Kanazawa, Atsuko; Ostendorf, Elisabeth; Kohzuma, Kaori; Hoh, Donghee; Strand, Deserah D.; Sato-Cruz, Mio; Savage, Linda; Cruz, Jeffrey A.; Fisher, Nicholas; Froehlich, John E.; Kramer, David M. (Frontiers in Plant Science, 2017)
In wild type plants, decreasing CO2 lowers the activity of the chloroplast ATP synthase, slowing proton efflux from the thylakoid lumen resulting in buildup of thylakoid proton motive force (pmf). The resulting acidification of the lumen regulates both light harvesting, via the qE mechanism, and photosynthetic electron transfer through the cytochrome b6f complex. Here we show that the cfq mutant of Arabidopsis, harboring single point mutation in its γ-subunit of the chloroplast ATP synthase, increases the specific activity of the ATP synthase and disables its down-regulation under low CO2. The increased thylakoid proton conductivity (gH+) in cfq results in decreased pmf and lumen acidification, preventing full activation of qE and more rapid electron transfer through the b6f complex, particularly under low CO2 and fluctuating light. These conditions favor the accumulation of electrons on the acceptor side of PSI, and result in severe loss of PSI activity. Comparing the current results with previous work on the pgr5 mutant suggests a general mechanism where increased PSI photodamage in both mutants is caused by loss of pmf, rather than inhibition of CEF per se. Overall, our results support a critical role for ATP synthase regulation in maintaining photosynthetic control of electron transfer to prevent photodamage.